Phytantriol based liquid crystal provide sustained release of anticancer drug as a novel embolic agent. (1st February 2016) - Qin, Lingzhen; Mei, Liling; Shan, Ziyun; Huang, Ying; Pan, Xin; Li, Ge; Gu, Yukun; Wu, Chuanbin
Abstract: Phytantriol has received increasing amount of attention in drug delivery system, however, the ability of the phytantriol based liquid crystal as a novel embolic agent to provide a sustained release delivery system is yet to be comprehensively demonstrated. The purpose of this study was to prepare a phytantriol-based cubic phase precursor solution loaded with anticancer drug hydroxycamptothecine (HCPT) and evaluate its embolization properties, in vitro drug release and cytotoxicity. Phase behavior of the phytantriol–solvent–water system was investigated by visual inspection and polarized light microscopy, and no phase transition was observed in the presence of HCPT within the studied dose range. Water uptake by the phytantriol matrices was determined gravimetrically, suggesting that the swelling complied with the second order kinetics. In vitro evaluation of embolic efficacy indicated that the isotropic solution displayed a satisfactory embolization effect. In vitro drug release results showed a sustained-release up to 30 days and the release behavior was affected by the initial composition and drug loading. Moreover, the in vitro cytotoxicity and anticancer activity were evaluated by MTT assay. No appreciable mortality was observed for NIH 3T3 cells after 48 h exposure to blank formulations, and the anticancer activity of HCPT-loaded formulations to HepG2 and SMMC7721 cells was strongly dependent on the drug loading and treatment time. Taken together, these results indicate that phytantriol-based cubic phase embolic gelling solution is a promising potential carrier for HCPT delivery to achieve a sustained drug release by vascular embolization, and this technology may be potential for clinical applications.